USING ENVIRONMENTAL AND SOCIAL SAFEGUARDS FRAMEWORK FOR IMPROVING PROJECTS EVALUATION METHODOLOGY IN KAZAKHSTAN - Rakhimova, Gulmira; Shalmanov, Adilzhan; Mendagaziyeva, Sabina (Nazarbayev University, Graduate School of Public Policy, 2021)
This research aims at the evaluation and comparison of the environmental and social standards and practices of national, regional, and international development institutions operating in Kazakhstan on enforcing environmental and social goals. Since the main source of funding for industrial projects of large scale is not private sector, but development institutions, the requirements of these financing parties towards projects to pursue environmental and social goals aside of pure profit seeking are important instrument for the promotion of environmental and social awareness into general business practice. The research is based on the qualitative approach as the main research method. Primary data was collected through semi-structured interviews while secondary data was collected using the open resources of the development institutions. We conducted comparative analysis of the above-mentioned standards, mechanisms and practices using the primary and secondary data. The research findings show that environmental and social agendas do not receive sufficient explicit attention from the development institutions actively investing in industrialization in Kazakhstan. The practice used by UN agencies namely the UNDP based on the Environmental and Social Safeguards developed by International Finance Corporation (IFC) has proven its operational efficiency in local conditions as per results of survey and further adaptation of this framework would be instrumental for improvement of this situation.
Keywords: Environmental and Social Safeguards; Sustainable Development Goals; Type of access: Open Access